Bottom ash from combustion of chicken manure as a fertiliser material - Bernal, María Pilar; Álvarez-Robles, María José; Bernal-Molina, Paula; Clemente, Rafael (Frontiers in Sustainable Food Systems, 2024)
The accumulation of excess manure and the energy costs of the buildings housing the animals are the most important problems that chicken farms have to face nowadays. The combustion of chicken manure to obtain thermal energy for animal holdings has been demonstrated through the research project AVIENERGY, in Spain. To ensure the circularity of the process, the combustion by-product, bottom ash, needs to be recycled and used. This work studies the agricultural use of ash from chicken manure combustion as a fertiliser product and determines its capacity for mineral fertiliser substitution. Ashes from co-combustion of chicken (broiler) manure with wood at different proportions were chemically analysed to determine their nutrient concentrations and availabilities. Then, one ash sample was used as a fertiliser for lettuce cultivation in a pot experiment. Different application rates were tested according to the phosphorus (P) content of the ash, being equivalent to 50, 65, 80 and 100% of the standard inorganic P fertilisation. The results indicate that the ash from combustion of chicken manure meets the requirements for inclusion in the fertiliser component material category ‘CMC 13’, and can be used for the preparation of fertiliser ‘PFC 1(C)(I)(a)(ii): Compound Solid Inorganic Macronutrient Fertiliser (multi-nutrients)’, and also possesses characteristics of “PFC 2: Liming Material” according to the EU legislation for fertiliser products. Although plant production was slightly reduced with ash fertilisation, the ashes reached a fertiliser capacity able to substitute 80% of the mineral P fertiliser, with a liming capacity of 30%. Hence, the ash from chicken manure combustion could be applied to soil, especially if acidic, in partial substitution of mineral fertilisers, to supply P.